Frequency of Paresthesia with Zygomaticomaxillary Complex Fracture - Hilal, Rashida; Malik, Zainab Mushtaq; Hassan, Raheel; Akram, Umair; Yasmeen, Rehana; Sharifullah, Faryal; Bukhari, Abid (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Paresthesia is defined as alteration in local sensibility, accompanied with numbness, tingling, or unpleasant sensation caused by nerve injury Aim: To determine the frequency of paresthesia with zygomaticomaxillary complex (ZMC) fractures. Methodology: Descriptive case series was carried out at Department of Dentistry, Ayub Teaching Hospital, Abbottabad from 20th December 2021 to 20th June 2022. One hundred and sixty-four patients of both genders with ZMC fracture confirmed clinically and radiographically were included. The zygomatic region was clinically examined for presence of zygomatic complex fracture and associated paresthesia. Results: The age range was from 20 to 80 years with mean age of 37.061±9.93 years and mean duration of injury was 8.457±2.4 6days. Male patients were 90.9% and females were 9.1%. Paresthesia was observed in 18.3% patients. The study involved patients aged 20-80 years, with a mean age of 37.061 years and a mean duration of 8.457 days. Males were 90.9%, with 46.3% left side injuries, and 18.3% experienced paresthesia. Practical implication: The study highlights the importance of assessing fractures and identifying nerve compression to mitigate sensory complications, emphasizing the need for early-stage treatment. Conclusion: The compression of infraorbital nerve leading to paresthesia was more common in displaced fractures of zygomaticomaxillary complex fractures.